Uncovering a causal connection between the Lachnoclostridium genus in fecal microbiota and non-alcoholic fatty liver disease: a two-sample Mendelian randomization analysis - Dai, Wanhui; Cai, Dandong; Zhou, Shuai; Li, Ang; Xie, Jinsong; Zhang, Jie (Frontiers in Microbiology, 2023)
Background: Previous observational studies have indicated an imbalance in gut microbiota may contribute to nonalcoholic fatty liver disease (NAFLD). However, given the inevitable bias and unmeasured confounders in observational studies, the causal relationship between gut microbiota and NAFLD cannot be deduced. Therefore, we employed a two-sample Mendelian randomization (TSMR) study to assess the causality between gut microbiota and NAFLD.The gut microbiota-related genome-wide association studies (GWAS) data of 18,340 individuals were collected from the international consortium MiBioGen. The GWAS summary data for NAFLD from the Anstee cohort (1,483 cases and 17,781 controls) and the FinnGen consortium (894 cases and 217,898 controls) were utilized in the discovery and verification phase, respectively. The inverse variance weighted (IVW) method was used as the principal method in our Mendelian randomization (MR) study, with sensitivity analyses using the MR-Egger, weighted median, simple mode, and weighted mode methods. The MR-Egger intercept test, Cochran's Q test, and leave one out analysis were conducted to identify heterogeneity and pleiotropy. Moreover, a fixed effects meta-analysis was conducted to verify the robustness of the results.Results: Gene prediction results showed that four gut microbiota at the genus level were causally associated with NAFLD in the GWAS conducted by Anstee et al. The relative abundance of Intestinimonas (OR: 0.694, 95%CI: 0.533-0.903, P=0.006, IVW), Lachnoclostridium (OR: 0.420, 95%CI: 0.245-0.719, P=0.002, IVW) and Senegalimassilia (OR: 0.596, 95%CI: 0.363-0.978, P=0.041, IVW) were negatively associated with NAFLD. The relative abundance of Ruminococcus1 (OR: 1.852, 95%CI: 1.179-2.908, P=0.007, IVW) was positively correlated with NAFLD. Among them, the Lachnoclostridium genus was validated in FinnGen GWAS (OR: 0.53, 95%CI: 0.304-0.928, P=0.026, IVW). The Lachnoclostridium genus was also significantly associated with NAFLD risk in the meta-analyses (OR: 0.470, 95%CI: 0.319-0.692, P=0.0001, IVW). No heterogeneity or pleiotropy was observed.This study provided new evidence for the relationship between Lachnoclostridium genus and NAFLD, suggesting that augmentation of the relative abundance of Lachnoclostridium genus through the oral administration of probiotics or fecal microbiota transplantation could be an effective way to reduce the risk of NAFLD.